A psychometric evaluation of the Gender Bias in Medical Education Scale. Issue 1 (December 2016) - Parker, Rhiannon; Parker, Philip; Larkin, Theresa; Cockburn, Jon
Abstract Background Gender bias within medical education is gaining increasing attention. However, valid and reliable measures are needed to adequately address and monitor this issue. This research conducts a psychometric evaluation of a short multidimensional scale that assesses medical students' awareness of gender bias, beliefs that gender bias should be addressed, and experience of gender bias during medical education. Methods Using students from the University of Wollongong, one pilot study and two empirical studies were conducted. The pilot study was used to scope the domain space (n = 28). This initial measure was extended to develop the Gender Bias in Medical Education Scale (GBMES). For Study 1 (n = 172), confirmatory factor analysis assessed the construct validity of the three-factor structure (awareness, beliefs, experience) and enabled deletion of redundant items. Study 2 (n = 457) tested the generalizability of the refined scale to a new sample. Combining Study 1 and 2, invariance testing for program of study and gender was explored. The relationship of the GBMES to demographic and gender politics variables was tested. The results were analyzed in R using confirmatory factor analysis and Multiple-Indicator-Multiple-Indicator-Cause models. Results After analysis of the responses from the original 16-item GBMES (Study 1), a shortened measure of ten items fitted the data well (RMSEA = .063; CFI = .965; TLI = .951; Mean R-square of items = 58.6 %; reliability: .720–.910) and was found to generalize to a new sample in Study 2 (RMSEA = .068; CFI = .952; TLI = .933; Mean R-square of items = 55.9 %; reliability: .711–.892). The GBMES was found to be invariant across studies, gender, and program of study. Female students and those who supported gender equality had greater agreement for each of the factors. Likewise, postgraduate students reported higher scores on experience of gender bias than undergraduate students. Conclusion The GBMES provides a validated short multidimensional measure for use in research and policy. Given its good reliability across different target populations and its concise length, the GBMES has much potential for application in research and education to assess students' attitudes towards gender bias.